Identity and internationalization in catholic universities : exploring institutional pathways in context - Wit, Hans de (Leiden Boston Brill, 2018)
Identity and Internationalization in Catholic Universities explores the relationship between Catholic identity, mission, and internationalization in Catholic universities of different types and located in different contexts. Internationalization is a key concern for universities working to achieve their goals in different regions of the world but without neglecting their identity. There are many universities that consider themselves related to the Roman Catholic faith and many other universities with Christian affiliations. It is well known that Catholic universities have unique missions, such as the formation of individuals inspired by a religious conviction to serve society and the church.
Keywords: Universidades de la Iglesia; Globalización; Identidad; Colegios católicos